(untitled) (Eurasian Scientific Herald, 2023)
In this article, the didactic games for spending moments of beautiful writing in primary class mother tongue lessons: "Who can find the fastest?" game, "Illustrative didactic game", "Thinking game", "Finding the place of the word” It allows you to get information about didactic games such as how to use them, and their importance in forming beautiful writing of students.